SecA is required for membrane targeting of the cell division protein DivIVA in vivo - Halbedel, Sven; Kawai, Maki; Breitling, Reinhard; Hamoen, Leendert W. (Frontiers in Microbiology, 2014)
The conserved protein DivIVA is involved in different morphogenetic processes in Gram-positive bacteria. In Bacillus subtilis, the protein localises to the cell division site and cell poles, and functions as a scaffold for proteins that regulate division site selection, and for proteins that are required for sporulation. To identify other proteins that bind to DivIVA, we performed an in vivo cross-linking experiment. A possible candidate that emerged was the secretion motor ATPase SecA. SecA mutants have been described that inhibit sporulation, and since DivIVA is necessary for sporulation, we examined the localisation of DivIVA in these mutants. Surprisingly, DivIVA was delocalised, suggesting that SecA is required for DivIVA targeting. To further corroborate this, we performed SecA depletion and inhibition experiments, which provided further indications that DivIVA localisation depends on SecA. Cell fractionation experiments showed that SecA is important for binding of DivIVA to the cell membrane. This was unexpected since DivIVA does not contain a signal sequence, and is able to bind to artificial lipid membranes in vitro without support of other proteins. SecA is required for protein secretion and membrane insertion, and therefore its role in DivIVA localisation is likely indirect. Possible alternative roles of SecA in DivIVA folding and/or targeting are discussed.